2011
DOI: 10.1111/j.1365-2141.2011.08732.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand Syndrome in congenital heart disease: does it promote an increased bleeding risk?

Abstract: Keywords: B cell activating factor, ELISA, thrombotic thrombocytopenic purpura, a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13, rituximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Some authors have observed very low rates of bleeding in patients with AVWS secondary to CPD (Casonato et al , ; Loeffelbein et al , ). Conversely, some authors have reported increased rates of post‐operative and intracranial bleeding in the setting of congenital heart disease and/or use of ventricular assist devices (Onimoe et al , ; Jones et al , ). In our cohort, most patients exhibited only mild bleeding symptoms; the one patient that underwent a double‐lung transplantation did sustain peri‐operative haemorrhage despite having received a VWF concentrate.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have observed very low rates of bleeding in patients with AVWS secondary to CPD (Casonato et al , ; Loeffelbein et al , ). Conversely, some authors have reported increased rates of post‐operative and intracranial bleeding in the setting of congenital heart disease and/or use of ventricular assist devices (Onimoe et al , ; Jones et al , ). In our cohort, most patients exhibited only mild bleeding symptoms; the one patient that underwent a double‐lung transplantation did sustain peri‐operative haemorrhage despite having received a VWF concentrate.…”
Section: Discussionmentioning
confidence: 99%
“…cause high shear stress. Acquired von Willebrand syndrome IIA has been reported in patients with hypertrophic obstructive cardiomyopathy 14) , congenital structural cardiac diseases 15) , pulmonary hypertension 16) , and mitral stenosis 17) . Furthermore, mechanical circulatory support has drastically advanced and contributes much to the treatment of severe heart failure and it is inevitable that high shear stress is generated inside the pumps used in the devices.…”
Section: Treatment and Prognosis Of Patients With Heyde's Syndromementioning
confidence: 99%
“…Ventricular Septal Defects-There have been reports of AVWS in patients with congenital ventricular septal defects with resolution following corrective surgery [47].…”
Section: Prevalence Of Avws In Cardiovascular Diseasementioning
confidence: 99%